Sekolah Cinta Indonesia sebagai Sarana Pembinaan Politik PKS Kota Banda Aceh - Ziaulhaq, Muhammad (Program Studi Ilmu Politik, Universitas Syiah Kuala, Banda Aceh, 2024)
The Prosperous Justice Party (PKS) has become the dominant national political force in the city of Banda Aceh, establishing itself as a cadre party to be reckoned with in the realm of Indonesian politics. The Islamic ideological orientation has led PKS to a parliamentary seat, showing its commitment to strict development and cadre formation. Through initiatives such as the Indonesian Love School, PKS nominates 30 legislative candidates (Caleg) from internal cadres, maintaining its essence as a party dominated by cadres. This research aims to determine the extent of the PKS cadre formation process in educating cadres as well as the impact on the cadres involved. Using the descriptive-qualitative method, data analysis is carried out through observation, documentation, and interviews. The theory of political parties and political cadre formation is the main basis for this research. The results of this research show that PKS in Banda Aceh City plays an important role in the cadre formation process through programs such as the Indonesian Love School. They carry out a cadre formation program by holding political outreach, following the provisions of the party's AD/ART, which includes member recruitment, tiered development, and training through the Member Development Unit. The influence of this cadre formation process starts with educational institutions, producing cadres who are ideologically strong and able to integrate Islamic values with Pancasila, and this program has an influence on cadres in terms of political education regarding ethics, leadership, and a deep understanding of politics and democracy. Sekolah Cinta Indonesia is expected to increase its acceleration and quality by strengthening its cadre base through the cadre formation process. Strengthening in-depth material will affect the quality of cadres, which will also affect the quality and existence of politics Abstrak Partai Keadilan Sejahtera (PKS) telah menjadi kekuatan politik nasional yang dominan di Kota Banda Aceh, mengukuhkan dirinya sebagai partai kader yang diperhitungkan dalam ranah politik Indonesia. Orientasi ideologi Islam telah mengantar PKS ke kursi parlemen, memperlihatkan komitmennya terhadap pembinaan dan pengaderan yang ketat. Melalui inisiatif seperti Sekolah Cinta Indonesia, PKS mencalonkan 30 Calon Legislatif (Caleg) dari kader internal, menjaga esensi sebagai partai yang didominasi oleh kader. Penelitian ini bertujuan untuk mengetahui sejauh mana proses kaderisasi PKS dalam mendidik kader, serta memahami dampaknya terhadap kader yang terlibat. Dengan metode kualitatif deskriptif, analisis data dilakukan melalui observasi, dokumentasi, dan wawancara. Teori partai politik dan kaderisasi politik menjadi landasan utama penelitian ini. Hasil penelitian ini menunjukkan PKS di Kota Banda Aceh memegang peranan penting dalam proses kaderisasi melalui program seperti Sekolah Cinta Indonesia. Mereka menjalankan program kaderisasi dengan mengadakan sosialisasi politik, mengikuti ketentuan AD/ART partai, yang mencakup rekrutmen anggota, pembinaan berjenjang, dan pelatihan melalui Unit Pembinaan Anggota. Pengaruh dari proses kaderisasi ini dimulai dari lembaga pendidikan, menghasilkan kader yang kuat secara ideologis dan mampu mengintegrasikan nilai-nilai Islam dengan Pancasila dan Program ini memberikan pengaruh terhadap kader dari segi pendidikan politik tentang etika, kepemimpinan, dan pemahaman mendalam tentang politik dan demokrasi. Sekolah Cinta Indonesia diharapkan untuk meningkatkan akselerasinya dan kualitasnya dengan memperkuat basis-basis kader lewat proses kaderisasi. Penguatan materi yang mendalam bakal mempengaruhi kualitas kader yang juga mempengaruhi kualitas dan eksistensi politik